Prognostic significance of semiautomatic quantification of left ventricular long axis shortening in systemic light-chain amyloidosis - Riffel, Johannes; Mereles, Derliz; Emami, Mostafa; Korosoglou, Grigorios; Kristen, Arnt; Aurich, Matthias; Voß, Andreas; Schönland, Stefan; Hegenbart, Ute; Hardt, Stefan; Katus, Hugo; Buß, Sebastian Johannes (Amyloid, 2015)
Aims: To assess left ventricular long axis shortening (LAS) in patients with AL amyloidosis as a potential predictor for outcome.Methods and results: We performed a de novo echocardiographic analysis of LAS in 120 patients with biopsy-proven AL amyloidosis evaluated at first presentation before specific treatment. Additionally, 47 control subjects were analyzed retrospectivly. LAS was measured using a semiautomatic tissue motion annular displacement software algorithm (TMAD). LAS was significantly better than ejection fraction (EF) (p < 0.0001) and M-mode-derived mitral annular plane systolic excursion (MAPSE) (p < 0.05) discriminating AL patients from control subjects, while being non-inferior compared to tissue Doppler-derived peak systolic mitral annular velocity. One year outcome analysis in patients with AL amyloidosis showed that LAS remained the only significant echocardiographic parameter (HR:0.76; p < 0.005) in a multivariable Cox regression model of echocardiographic values. In a comprehensive clinical model, LAS (HR:0.72, p < 0.0001), cardiac troponin-T (HR:2.86, p < 0.01) and free light chain difference (HR:1.00; p < 0.05) were independently associated with the outcome. Assessment of LAS led to a significant integrated discrimination improvement and offered incremental information compared to EF and biomarkers. The cut-off value for LAS discriminating the endpoint was 5.8%.Conclusion: LAS was an independent predictor of survival within the first year and offers incremental information in patients with AL amyloidosis evaluated prior to specific treatment.
Published online: 10 Dec 2014
Gesehen am 18.06.2020